Cell Growth on Different Types of Ultrananocrystalline Diamond Thin Films - Orlando Auciello; Amina S. Woods; Albert J. Schultz; Liaohai Chen; Qiaoling Jin; Bing Shi (Journal of Functional Biomaterials, 2012)
Unique functional materials provide a platform as scaffolds for cell/tissue regeneration. Investigation of cell-materials’ chemical and biological interactions will enable the application of more functional materials in the area of bioengineering, which provides a pathway to the novel treatment for patients who suffer from tissue/organ damage and face the limitation of donation sources. Many studies have been made into tissue/organ regeneration. Development of new substrate materials as platforms for cell/tissue regeneration is a key research area. Studies discussed in this paper focus on the investigation of novel ultrananocrystalline diamond (UNCD) films as substrate/scaffold materials for developmental biology. Specially designed quartz dishes have been coated with different types of UNCD films and cells were subsequently seeded on those films. Results showed the cells’ growth on UNCD-coated culture dishes are similar to cell culture dishes with little retardation, indicating that UNCD films have no or little inhibition on cell proliferation and are potentially appealing as substrate/scaffold materials. The mechanisms of cell adhesion on UNCD surfaces are proposed based on the experimental results. The comparisons of cell cultures on diamond-powder-seeded culture dishes and on UNCD-coated dishes with matrix-assisted laser desorption/ionization—time-of-flight mass spectroscopy (MALDI-TOF MS) and X-ray photoelectron spectroscopy (XPS) analyses provided valuable data to support the mechanisms proposed to explain the adhesion and proliferation of cells on the surface of the UNCD platform.